Morphological and molecular evidence of cryptic speciation in sympatric colour morphotypes of Mycale (Carmia) cecilia (Porifera: Poecilosclerida) from the Mexican Pacific - Ana Castillo-Páez; Raúl Llera-Herrera; José Antonio Cruz-Barraza (Scientia Marina, 2024)
Identifying cryptic species is pivotal for understanding marine biodiversity and optimizing strategies for its conservation. A robust understanding of poriferan diversity is a complex endeavour. It has also been extremely hampered by the high phenotypic plasticity and the limited number of diagnostic characters. Mycale (Carmia) cecilia has different body colours, even among individuals living together. We tested whether the colour variation could be due to polymorphism, phenotypic plasticity or cryptic speciation. Phylogenetic reconstructions of nuclear and mitochondrial loci were congruent. Individuals of different body colour did not cluster together and had high levels of genetic divergence. Furthermore, the green morphotype clustered in almost all reconstructions with Mycale (C.) phyllophila, as both showed higher gene similarity at the transcriptomic level (public transcriptome). Morphologically, the green individuals consistently showed discrepancies from the red ones. These results suggest that all individuals with the same body colour, either red or green, correspond to the same species, while individuals with different body colours probably belong to different species. These results reveal high levels of morphologic and genetic diversity, which could have important implications for what is known as M. (C.) cecilia and the Mycalidae systematics.